2020
DOI: 10.1111/mpp.12989
|View full text |Cite
|
Sign up to set email alerts
|

AvrE1 and HopR1 from Pseudomonas syringae pv. actinidiae are additively required for full virulence on kiwifruit

Abstract: Pseudomonas syringae is a model plant pathogen for studying bacterial pathogenicity, in particular the molecular mechanisms of disease establishment. The P. syringae species complex is currently represented by 64 pathovars, with each pathovar identified as infecting a select host plant genus, but often possessing the capacity to infect more, being restricted by plant immunity and environmental parameters (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…This may be attributed to the possible role of HopAU1 as a no virulence protein in the M228 T3SE repertoire. More evidences showed that three T3SEs, HopR1, AvrE1 and HopZ5, contributed almost 80% to Psa3 virulence [ 28 , 41 ], further supporting the no-virulence protein role of in Psa .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This may be attributed to the possible role of HopAU1 as a no virulence protein in the M228 T3SE repertoire. More evidences showed that three T3SEs, HopR1, AvrE1 and HopZ5, contributed almost 80% to Psa3 virulence [ 28 , 41 ], further supporting the no-virulence protein role of in Psa .…”
Section: Discussionmentioning
confidence: 91%
“…Studies on Psa T3SEs have performed subcellular localization and transient expression to select several T3SEs triggered HR in N. benthamiana [ 27 ]. In addition, AvrE1 Psa and HopR1 Psa have been shown to be essential for full virulence, while HopM1 (belonging to the AvrE/HopM family) exhibits functional redundancy [ 28 , 29 ]. Additional research has focused on the recognition mechanism of Psa T3SEs in model plants.…”
Section: Introductionmentioning
confidence: 99%
“… AvrE1 KP808_06005 Pseudomonas syringae pv. Lachrymans (MAFF301315) 1571 98.6 Cytoplasm two-component system sensor histidine Required for in planta growth and lesion production [ 23 ]. HopA1 KP808_06050 Pseudomonas syringae pv.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a recent comparative transcriptional profiling exercise revealed that T3SS genes were strongly activated in Psa3 responding to apoplast-like conditions, compared with those in Psa1 and Psa2, which are responsible for the epidemics in Japan and Korea, respectively ( Vandelle et al, 2020 ). Several T3Es secreted by the T3SS apparatus have been reported to be involved in pathogenicity in Psa3, such as HopZ5 ( Zhao et al, 2019a ), AvrE1, and HopR1 ( Jayaraman et al, 2020 ). In this study, we found that T3Es HopBB1-1 and HopBB1-2 were incomplete in Psa3 isolate G35, which showed attenuated HR-eliciting activity in N. benthamina leaves and moderate pathogenicity in host plants.…”
Section: Discussionmentioning
confidence: 99%